Pengaruh Komisaris Independen, Cash Management, dan Net Working Capital Terhadap Cash Holding Pada Perusahaan Properti dan Real Estate Tahun 2021-2023 - Diva Ayu Pusvitasari; Risa Nurmala Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine and analyze the influence of independent commissioners, cash management, using cash flow and capital expenditure as measures, and net working capital on cash holdings. The sample was selected using a purposive sampling method based on specific criteria. The sample used in this study consists of 62 property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research method used is a quantitative approach and multiple regression analysis. Data collection techniques were conducted using secondary data from financial statements and annual reports of companies listed on the Indonesia Stock Exchange (IDX). The results of this study indicate that cash flow has a positive effect on cash holdings. Meanwhile, independent commissioners, capital expenditure, and net working capital have a negative effect on cash holdings.